Color pattern polymorphism and chromatic aberrancies in Physalaemus fernandezae (Anura, Leptodactylidae) - Cajade, Rodrigo (2024)
Skin coloration patterns in anurans could be markedly varied due to color pattern polymorphism and the occurrence of chromatic aberrancies. Knowledge about this variability allows to understand prey-predator relationships, contributes to the characterization of taxonomic groups, and may reflects genetic variability. We report herein a characterization of dorsal and ventral color pattern polymorphisms in the Neotropical frog Physalaemus fernandezae, and the finding of chromatic aberrancies in wild tadpoles. We assessed the sexual variation of four dorsal color morphs (Broadband, Reticulate, Vertebral Line, Uniform with Urostylar Line) and two ventral color morphs (Immaculate and Maculate). We found no association about the co-occurrence of different ventral and dorsal color patterns, also regardless sex, suggesting independent evolution forces influencing on them. In addition, we found geographic color pattern variation. A color aberrancy considered as leucism was observed in tadpoles, and is reported for the first time in P. fernandezae. We suggest that the patterns frequency distributions are suggestive of an apostatic selection mechanism for the color polymorphism in P. fernandezae.